Answer:
3x + 2y = 17
2x + 5 y = 26
Step-by-step explanation:
3x + 2y = 17 }
2x + 5 y = 26}
x - 3y = - 9
x = -9 + 3y
=> 2 (-9+3y)+5y=26
-18+6y+5y=26
-18+11y=26
11y=26+18
11y=44
y= 4
3x + 8=17
3x = 17 - 8
3x = 9
x = 9 : 3
x = 3
Answer:
u can use the hit and trial method for this
Answer:
I don’t like math
Step-by-step explanation:
Answer:
Step-by-step explanation:
e^ lnx = x
e^ ln5 = 5
e^ ln 3x = 3x
I think you get the idea... e is an inverse operation to ln :o
I did get the one in the tux ♂️ and the other one ☝️